Novel Bioactivity of Ellagic Acid in Inhibiting Human Platelet Activation. (21st February 2013) - Chang, Yi; Chen, Wei-Fan; Lin, Kuan-Hung; Hsieh, Cheng-Ying; Chou, Duen-Suey; Lin, Li-Jyun; Sheu, Joen-Rong; Chang, Chao-Chien
Abstract : Pomegranates are widely consumed either as fresh fruit or in beverage form as juice and wine. Ellagic acid possesses potent antioxidative properties; it is known to be an effective phytotherapeutic agent with antimutagenic and anticarcinogenic qualities. Ellagic acid (20 to 80  μ M) exhibited a potent activity in inhibiting platelet aggregation stimulated by collagen; however, it did not inhibit platelet aggregation stimulated by thrombin, arachidonic acid, or U46619. Treatment with ellagic acid (50 and 80  μ M) significantly inhibited platelet activation stimulated by collagen; this alteration was accompanied by the inhibition of relative [ Ca 2+ ] i mobilization, and the phosphorylation of phospholipase C (PLC) γ 2, protein kinase C (PKC), mitogen-activated protein kinases (MAPKs), and Akt, as well as hydroxyl radical (OH ● ) formation. In addition, ellagic acid also inhibited p38 MAPK and Akt phosphorylation stimulated by hydrogen peroxide. By contrast, ellagic acid did not significantly affect PKC activation and platelet aggregation stimulated by PDBu. This study is the first to show that, in addition to being considered a possible agent for preventing tumor growth, ellagic acid possesses potent antiplatelet properties. It appears to initially inhibit the PLCγ 2-PKC cascade and/or hydroxyl radical formation, followed by decreased phosphorylation of MAPKs and Akt, ultimately inhibiting platelet aggregation.